Quality Characteristics Of Symplocos Paniculata (Thunb.) Miq. Fruit Oil Obtained By Different Extraction Methods (Applied Biological Research, 2023)
The aim of present study was to develop an optimum extraction method for high  quality edible oil from Symplocos paniculata fruit. S. paniculata fruit oils were  extracted by three methods viz., cold pressing (PCP), subcritical extraction  (SBE) and Soxhlet extraction (SE). A comparative analysis was performed for their physiochemical properties, fatty acid composition and bioactive  substances. The oil extraction rate from SE, SBE and PCP was 36.6, 35.7 and  8.4%, respectively. Total unsaturated fatty acids present were in the range of  79.04-79.35% with 48.13-48.52% oleic acid, and 30.08-30.18% linoleic acid. The  ratio of saturated fatty acids to total unsaturated fatty acids was 0.26025~0.2652.  PCP extraction oil had the highest content of polyunsaturated fatty acids, while  SBE extracted oil had highest content of unsaturated fatty acids, along with rich  bioactive substances. Based on the criterion of extraction rate, oil composition  and bioactive substances, the SBE method appeared optimum method for  extracting high quality edible oil from S. paniculata fruits.
Keywords: Bioactive substances; fatty acids; oil extraction method; Symplocos paniculata